2005
DOI: 10.1093/jxb/eri235
|View full text |Cite
|
Sign up to set email alerts
|

NaCl alleviates polyethylene glycol-induced water stress in the halophyte species Atriplex halimus L.

Abstract: Atriplex halimus L. is a C4 xero-halophyte species well adapted to salt and drought conditions. To collect information on the physiological impact of low salt levels on their water-stress resistance, seedlings were exposed for 6 d to nutrient solution containing either 0% or 15% polyethylene glycol 10,000 (PEG), in the presence or in the absence of 50 mM NaCl. Similar experiments were performed with one PEG-resistant and one PEG-sensitive selected cell line exposed for 50 d to 0% or 15% PEG on standard Linsmai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
79
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 32 publications
16
79
1
2
Order By: Relevance
“…Martí nez et al (2005) ascribed improved growth at 50 mM NaCl to possible Na + enhancement of photosynthesis and sugar synthesis and/or transport. Boughalleb et al (2009) related enhanced growth to improvements in stomatal conductance, transpiration and CO 2 assimilation at moderate external NaCl levels (< 300 mM); Khedr et al (2011) suggested that vacuolar Na + accumulation increases cell volume and the photoassimilatory surface area of the leaves, stimulating growth.…”
Section: Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Martí nez et al (2005) ascribed improved growth at 50 mM NaCl to possible Na + enhancement of photosynthesis and sugar synthesis and/or transport. Boughalleb et al (2009) related enhanced growth to improvements in stomatal conductance, transpiration and CO 2 assimilation at moderate external NaCl levels (< 300 mM); Khedr et al (2011) suggested that vacuolar Na + accumulation increases cell volume and the photoassimilatory surface area of the leaves, stimulating growth.…”
Section: Salinitymentioning
confidence: 99%
“…Like other halophytes, A. halimus accumulates the ions responsible for salinity -Na + (Martí nez et al, 2005;Nemat Alla et al, 2012) and Cl -and other anions (Ben Ahmed et al, 1996;Ben Hassine et al, 2009) -in its tissues and is able to compartmentalise them in the vacuole due to efficient intracellular transport (Khedr et al, 2011). This osmotic adjustment (OA, the active intracellular accumulation of osmolytes) generates low values of tissue Ψ w ; even-lower coincident values of osmotic potential (Ψ s ) (e.g., -7.5 MPa; Bajji et al, 1998) maintain tissue turgor.…”
Section: Salinitymentioning
confidence: 99%
“…Essa observação indica que a resposta exibida por células isoladas ou por calos pode ser diferente daquela apresentada pela planta inteira. Alguns trabalhos têm demonstrado que uma resposta observada in vitro pode ter ou não relação com uma resposta da planta inteira (Bajji et al, 1998;Martinez et al, 2005). Essa diferença pode ser explicada pelo fato de a resistência ao estresse hídrico ser um caráter quantitativo, que envolve a expressão de diversos genes (Knight & Knight, 2001) e a ação de complexos mecanismos bioquímicos e fisiológicos, coordenados nos níveis de célula, tecido, órgão, planta inteira (Zhu, 2001 (2003), ao trabalhar com três cultivares de arroz, que diferem entre si quanto à resistência à seca e ao sal, observaram maior acúmulo de prolina nas radículas das cultivares tolerantes, expostas in vitro ao manitol e NaCl.…”
Section: Resultsunclassified
“…Tais proteínas podem ser sintetizadas "de novo" ou ter a expressão aumentada, em resposta ao estresse. Em cultura de tecidos, vários trabalhos têm sido realizados para esclarecer o papel de ambas as classes de solutos compatíveis (Bajji et al, 1998;Lutts et al, 2001;Martinez et al, 2005). Uma vez que muitos dos métodos empregados no melhoramento de espécies de propagação vegetativa utilizam a cultura de tecidos, a caracterização da resposta in vitro ao estresse hídrico é uma etapa indispensável em programas de melhoramento de plantas.…”
Section: Introductionunclassified
“…Martinez et al (2005) reported that in salt selected cell cultures of Brassica napus, B. juncea, Vigna radiata and Arabidopsis thaliana, tolerance to NaCl selected cell lines was considered as a general shift towards halophytic characteristics. On the other hand, restricted uptake of Na + and maintenance of K + level with enhanced growth under NaCl stress in LiCl adapted line could be the result of enhanced capacity of membranes for ionic discrimination like salt tolerance in glycophytes observed in NaCl tolerant cell lines of citrus, tobacco Medicago sativa, rice and M. sativa (Ben-Hayyim and Kochba, 1983;Shah et al, 1993), where the cells maintain a lower amount of Na + content under saline conditions.…”
Section: Discussionmentioning
confidence: 99%